Ciri, Peran, dan Kedudukan Seorang Istri terhadap Suami dalam Naskah Babad Awak Salira - Isep Bayu Arisandi; Titin Nurhayati Ma'mun; Undang Ahmad Darsa (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2021)
Abstract The entry of Islam in Tatar Sunda also influenced the written tradition that was present before. One of the results of cultural acculturation is the ancient manuscript Babad Awak Salira (BAS), which contains Islamic teaching values. The BAS manuscript is identified into the category of the Sundanese manuscript of the Pesantren literature. The teachings of morals contained in the BAS text relate to the characteristics of a woman, the role of a wife, and the position of a wife in Islamic view. The author chooses to use an Islamic perspective because the relationship between the discussion in the value of the content is analyzed with the wife and recommendation in Islamic teachings, as well as the relevance of the value of the content to the conditions of Islamic teachings that enter and affect the written tradition. The results showed the same correlation between the content values ​​contained in the BAS text and the content values ​​in Islamic teachings. In other findings, the BAS text contains high language, because the form of the text is a wawacan (poetry), however, the aesthetic value of past poetry forms does not hinder the delivery of the content value in the text. — Abstrak Masuknya Islam di Tatar Sunda turut memengaruhi tradisi tulis yang hadir sebelumnya. Salah satu hasil akulturasi budaya adalah naskah kuna Babad Awak Salira (BAS), yang mengandung nilai-nilai ajaran Islam. Naskah BAS teridenfikasi masuk ke dalam kategori naskah Sunda pustaka pesantren. Ajaran adab atau akhlak yang terkandung di dalam teks BAS berkaitan dengan ciri wanita salihah, peran seorang istri, dan kedudukan seorang istri dalam pandangan Islam. Penulis memilih menggunakan pandangan Islam, karena keterkaitan pembahasan dalam nilai kandungan dianalisis dengan anjuran istri dalam ajaran Islam, serta relevansi nilai kandungan dengan kondisi ajaran Islam yang masuk dan berpengaruh pada tradisi tulis. Hasil Penelitian menunjukkan korelasi yang sama antara nilai kandungan yang terdapat di dalam teks BAS, dengan nilai-nilai kandungan dalam ajaran Islam. Dalam temuan lain, teks BAS mengandung bahasa yang tinggi, karena bentuk teks merupakan sebuah wawacan (puisi), meskipun demikian, keterikan nilai estetis trhadap bentuk puisi masa lalu tidak menghambat penyampaian nilai kandungan dalam teks.